Derivation of new optical solitons for Biswas-Milovic equation with dual-power law nonlinearity using improved modified extended tanh-function method - Elsonbaty, Nivan M.; Badra, Niveen M.; Ahmed, Hamdy M.; Elsherbeny, Ahmed M. (Alexandria engineering journal, 2023)
Cubic-quartic optical solitons and other solutions for Biswas-Milovic equation with dual-power law nonlinearity are investigated using improved modified extended tanh-function method. Bright soliton solutions, dark soliton solutions, singular soliton solutions, singular periodic solutions, Jacobi elliptic solutions and hyperbolic solutions are extracted. Furthermore, some selected solutions are described graphically to demonstrate the physical nature of obtained solutions.